Dopamine D2 receptor-mediated epidermal growth factor receptor signaling regulates neurogenesis in the subventricular zone of adult brain - Yea Jue Kim; Byeong Jun Kang; Jihee Seo; Sion Kim; Eun-chang Lee; Ha-yeon Cho; Donghoon Kim; Im Joo Rhyu; Ja-Hyun Baik (Neurobiology of Disease, 2025)
Mechanisms underlying selective dopaminergic neuronal degeneration in Parkinson's disease (PD) remain unclear. Impaired adult neurogenesis has been implicated in PD pathology, but its molecular regulation is not fully understood. We previously reported that dopamine D2 receptor (D2R)-mediated epidermal growth factor receptor (EGFR) signaling is critical for dopaminergic neuron development. To analyze how alterations in the dopamine system, especially D2R signaling in association with EGFR, contribute to dopamine-related dysfunction in vivo, we established a D2R cell-specific EGFR-deleted animal model, Drd2-Cre; EGFRf/f mice. These mice displayed a significant reduction in motor coordination ability and a decrease in the number of dopaminergic neurons in the midbrain, which resembles the characteristics of PD. We observed a reduction in the number of newly generated cells in the subventricular zone (SVZ) of aged Drd2-Cre; EGFRf/f mice, suggesting that the absence of EGFR in D2R-expressing cells could induce altered adult neurogenesis in the SVZ. Furthermore, when we compared the effect of l-3,4-dihydroxyphenylalanine (l-DOPA) on SVZ proliferation in 6-OHDA-lesioned control EGFRf/f and Drd2-Cre; EGFRf/f mice, the Drd2-Cre; EGFRf/f mice exhibited hindered L-DOPA-induced SVZ proliferation, indicating that D2R–EGFR signaling is necessary for the dopaminergic regulation of SVZ neurogenesis. These findings suggest that D2R–EGFR signaling is essential for maintaining midbrain dopaminergic neuron integrity and supporting adult neurogenesis, highlighting this pathway as a potential therapeutic target for promoting endogenous regenerative responses in PD.